PENGARUH PROFITABILITAS, PERTUMBUHAN PENJUALAN, CAPITAL EXPENDITURE DAN LEVERAGE TERHADAP KEBIJAKAN DIVIDEN PERUSAHAAN PERTAMBANGAN SEKTOR BATUBARA TAHUN 2019-2024 - eka nurhayatun; Ahsan Sumantika (Akmenika: Jurnal Akuntansi dan Manajemen, 2026)
This study aims to examine the effect of profitability, sales growth, capital expenditure, and leverage on dividend policy in coal mining companies listed on the Indonesia Stock Exchange during the 2019–2024 period. A quantitative approach was employed using panel data regression analysis with purposive sampling, and the common effect model was applied as the estimation technique. Dividend policy was proxied by the dividend payout ratio, while profitability was measured using return on equity. The partial test results indicate that profitability has a positive and significant effect on dividend policy, whereas sales growth shows a negative and significant effect. In contrast, capital expenditure and leverage do not have a significant influence on dividend policy. Simultaneously, all independent variables significantly affect dividend policy. The coefficient of determination reveals that the explanatory power of the model remains relatively low, suggesting that dividend policy is also influenced by other factors beyond the proposed model. These findings imply that profitability and growth strategies play a crucial role in shaping dividend policy decisions in coal mining companies.